An examination of the integral nature of slavery in classical Greek states (2017)
This paper examines why slavery, despite what is now legally known to be its obnoxious status, was not only fundamental to the Classical Greek society but was also endorsed by its intellectual community that was renowned for advocating individual freedom and justice. By discussing the place of slaves among the Greeks, the paper posits that the people saw slavery as crucial to realising socio-economic as well as political goals. Hence, the Greeks came to terms with chattel slavery as one of the realities of human existence. While enslaving others could be an expression of a superior might, the paper reasons that the utilitarian motivations for it in the Classical period are obvious. Therefore, individuals, both rich and poor, saw slaves as part of household features, indispensable to meeting socio-economic needs or sensual gratification. The functional use of slaves also extended to the state, hence, Sparta and Athens got all the leisure needed for political and military activities from slaves being always at their service. The paper concludes with brief allusion to the Biblical Onesimus to describe the reality of slavery as integral part of the social order of the ancient society. In view of the modern situations of labour and sexual exploitation at the international level, it is added that, whether with legislation against slavery or what is sometimes insincerity in fighting it, slavery/slavery condition might remain a modern institution; patronised by both private and public figures as long as human values remain similar to the Greeks‘.